Análisis contable financiero en la cooperativa de ahorro y crédito Joyocoto Ltda., comunidad de Joyocoto, parroquia Guanujo, cantón Guaranda, provincia Bolívar, año 2011. - Cuji Lema, Patricia Isabel (2011)
In the present research is the analysis of financial statements and aims to propose an actual accounting process according to the administrative needs for improved decision-making of the credit union's “Joyocoto” Ltd. Currently the financial statements is one of the most important to get the results that reflect the economic performance within a cooperative, as it comes to be this much help in decision making for managers. The Cooperative has a problem affects how financial accounting analysis the correct and timely decision making. This research work is divided into three chapters the same as follows: Chapter 1. Topic is presented, background, problem, rationale, objectives and theoretical framework is divided into reference is about the history of the cooperative, geo reference the location of the entity, are conceptual terminology used and applied to it, they scientific definitions are taken from different authors of books that contributed to the development of this work. Chapter 2. Refers to the implementation of data collection, analysis and interpretation of data, hypothesis testing, conclusions and recommendations. Chapter 3. It details the proposal; the object of study is established to improve the accounting process and the application of a current chart of accounts asserting the efficacy and accuracy of accounting data according to the new law on cooperatives, satisfactory stability cooperative.